Suitability of electrolytes and anodic dissolution behavior of 17-4 PH stainless steel. (2022) - Thakur, Aruna; Tak, Mukesh; Mote, Rakesh G.
Abstract: 17-4 PH SS alloy finds widespread applications in turbine blades, power plants, marine and chemical industries. However, some of its mechanical properties such as high tensile and fatigue strength, good toughness, high hardness and formability make its machinability poor. Thus, non-conventional machining processes such as electrochemical micromachining (ECMM), which removes the material by chemical dissolution, has better potential to fabricate micro features of high surface quality. However, the ECMM behavior of 17-4 PH SS alloy has not been exhaustively explored yet. It is very important to understand the regular dissolution patterns to improve machining stability and machined surface quality. Therefore, the present work aims at studying the suitability of different electrolytes in ECMM process for the fabrication of micro features with better dimensional accuracy and surface quality on 17-4 PH SS alloy. The electrolytes used in the experimentation are an aqueous solution of NaBr, NaCl, NaNO3  and a compound aqueous solution of NaCl + NaNO3 . The performance characteristics such as radial overcut, dimple depth and some aspects of surface integrity have been investigated. Experimental results showed that better dimensional accuracy and surface quality have been achieved with NaCl + NaNO3  electrolyte owing to the combined properties of passive and non-passive electrolytes.